Variation in the use of active surveillance for low‐risk prostate cancer. Issue 1 (13th September 2017) - Löppenberg, Björn; Friedlander, David F.; Krasnova, Anna; Tam, Andrew; Leow, Jeffrey J.; Nguyen, Paul L.; Barry, Hawa; Lipsitz, Stuart R.; Menon, Mani; Abdollah, Firas; Sammon, Jesse D.; Sun, Maxine; et al.
Abstract : BACKGROUND: This study assessed the use of active surveillance in men with low‐risk prostate cancer and evaluated institutional factors associated with the receipt of active surveillance. METHODS: A retrospective, hospital‐based cohort of 115, 208 men with low‐risk prostate cancer diagnosed between 2010 and 2014 was used. Multivariate and mixed effects models were used to examine variation and factors associated with active surveillance. RESULTS: During the study period, the use of active surveillance increased from 6.8% in 2010 to 19.9% in 2014 (estimated annual percentage change, +28.8%; 95% confidence interval [CI],  + 19.6% to + 38.7%; P  = .002). The adjusted probability of active‐surveillance receipt by institution was highly variable. Compared with patients treated at comprehensive community cancer centers, patients treated at community cancer programs (odds ratio [OR], 2.00; 95% CI, 1.50‐2.67; P  < .001) and academic institutions (OR, 2.47; 95%, CI, 1.81‐3.37; P  < .001) had higher odds of receiving active surveillance. Compared with patients treated at very low‐volume facilities, patients treated at very high‐volume facilities had higher odds of receiving active surveillance (OR, 3.57; 95% CI, 1.94‐6.55; P  < .001). Patient and hospital characteristics accounted for 60.2% of the overall variation, whereas the treating institution accounted for 91.5% of the unexplained variability. CONCLUSIONS: Within this hospital‐based cohort, the use of active surveillance for low‐risk prostate cancer increased significantly over time. Significant variation was found in the use of active surveillance. Most of the variation was attributable to facility‐related factors such as the facility type, facility volume, and institution. Policies to achieve consistent and higher rates of active surveillance, when appropriate, should be a priority of professional societies and patient advocacy groups. Cancer 2018;124:55‐64 . © 2017 American Cancer Society . Abstract : There are significant variations in surveillance rates for low‐risk prostate cancer according to the facility type and between individual institutions. A significant increase in the use of active surveillance from 2010 to 2014 has been found.